Analisis Kinerja Ekspor Terhadap Pemulihan Ekonomi Indonesia - Maulida Arifina; Hendri Hermawan Adinugraha (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2022)
Abstract. This research aims to determine the contribution of exports to economic recovery, especially in Indonesia. The method used is in the form of a literature study, whose data collection techniques are carried out by processing research materials derived from books, literature, notes, and various reports related to the problem to be solved. In this research, a qualitative approach was used, and the data used were secondary data. The results of this study indicate that exports play an important role in economic recovery because exports have a positive effect on economic growth. Increased exports will encourage increased domestic production. Increased production will drive the domestic economy so that economic growth will increase. Abstrak. Penelitian ini bertujuan untuk mengetahui kinerja ekspor terhadap pemulihan ekonomi khususnya di Indonesia. Metode yang digunakan berupa studi kepustakaan dengan pendekatan kualitatif dan data yang digunakan berupa data sekunder. Hasil penelitian ini menunjukkan bahwa ekspor berperan penting dalam pemulihan ekonomi, dikarenakan ekspor berpengaruh positif terhadap pertumbuhan ekonomi . Ekspor yang meningkat akan mendorong peningkatan produksi dalam negeri. Produksi yang meningkat akan menggerakkan perekonomian dalam negeri sehingga pertumbuhan ekonomi meningkat.